GROWTH AND MORTALITY OF LAGODON RHOMBOIDES (PISCES: SPARIDAE) IN A TROPICAL COASTAL LAGOON IN NORTHWESTERN YUCATAN, MEXICO - Bonilla-Gómez, José Luis (2011)
Growth and mortality were estimated for the Lagodon rhomboides pinfish inhabiting La Carbonera, a tropical coastal lagoon on the northwestern coast of the Yucatan Peninsula, Mexico. A total of 448 juvenile and adult individuals were collected monthly between April 2009 and May 2010. The length-weight relationship was calculated and the monthly variation in the condition factor was analyzed. Growth was estimated through the von Bertalanffy growth equation using a length frequency analysis. In addition, mortality was estimated and analyzed. Results showed that fish caught were between 2.1 and 20.0 cm long with an average length of 9.42 cm. The length-weight relationship showed isometric growth. The von Bertalanffy growth model parameters were: L∞ = 21.0 cm, W∞ = 163.46 g, k = 1.1 year-1 and t0 = - 0.158 years. Instantaneous mortality rates were 2.11 and 2.61 year-1 as estimated by the method used. According to the results, growth estimates of L. rhomboides along the northwestern coast of Yucatan are higher than those found in the population studied in Florida, suggesting a strong influence of environmental conditions in the growth pattern of this species. This study provides the first growth and mortality estimates for L. rhomboides in the Yucatan Peninsula, which is relevant for the proper implementation of conservation measures for this species.